Endangered African Knowledges and the Challenge of Modernity: An Igbo Response - Donald Mark Ude (Routledge, 2024)
This book presents an innovative African philosophical response to coloniality and the attendant epistemicide of Africa's knowledge systems, drawing on Igbo thinking. This book argues that theorizing modernity requires a critical conversation between African and Western scholarship, in order to unpack its links with coloniality and the subjugation of Africa's indigenous knowledges. In setting out this discussion, the book also connects with Latin American scholarship, demonstrating how the modern world is structured to marginalize and destroy knowledges from across the Global South. This book draws on Igbo epistemic resources of solidarity thinking, positioned in contrast to capitalist knowledge-patterns, thereby providing an important Africa-driven response to modernity and coloniality. This book concludes by arguing that the Igbo sense of solidarity is useful and relevant to modern contexts and thus constitutes a vital resource for a less disruptive, more balanced, and more wholesome modernity. At a time of considerable global crises, this book makes an important contribution to philosophy both within Africa and beyond.
Keywords: 300; Modernity; Postcoloniality; Postcolonial; Decoloniality; Decolonial; Nigeria; Indigenous Knowledges; Indigeneity; Race; Africana Studies; Epistemology; Igbo; Subaltern; Transmodernity; Identities